Increasing support for the next generation of clinical trials leaders. Issue 1 (December 2016) - Thompson, Peter; Fenton, James; Cotterill, Lisa; Neilson, James
Abstract The National Institute for Health Research (NIHR) has identified a gap in the number of people it funds who are on a pathway to become future leaders of clinical trials, compared to how much the NIHR invests in clinical trials. In order to support the clinical trials of tomorrow, it is vital that the right people are supported now to lead these trials. To address this issue, NIHR organised a workshop with key stakeholders to understand the barriers to embarking on a clinical trials career and explore initiatives to increase capacity and capability in clinical trials. The output from the workshop was a set of recommendations which NIHR is now considering to shape future support.